Implementation and performance of haemovigilance systems in 10 sub-saharan African countries is sub-optimal - Washington T. Samukange; Verena Kluempers; Manvi Porwal; Linda Mudyiwenyama; Khamusi Mutoti; Noel Aineplan; Helga Gardarsdottir; Aukje K. Mantel-Teeuwisse; C. Micha Nuebling (BMC, 2021)
Abstract Background Haemovigilance is an important element of blood regulation. It includes collecting and evaluating the information on adverse events resulting from the use of blood and blood components with the aim to improve donor and patient safety. We describe the results of the pilot of the integrated GBT+ Blood for the haemovigilance function in 10 sub-Saharan African countries. Methods We piloted the integrated WHO Global Benchmarking Tool plus Blood (GBT+ Blood) to assess the haemovigilance function of national regulatory authorities (NRAs) in Ethiopia, Kenya, Malawi, Nigeria, Liberia, Rwanda, South Africa, Tanzania, Uganda, and Zimbabwe. Data obtained from documents and face to face interviews were used to determine the status of implementation and performance of the following six indicators; legal provisions regulations and guidelines, organisation and governance, human resources, regulatory processes, transparency and accountability and finally, monitoring progress and assessing impact, by estimating median scores across 20 sub-indicators. In addition, a cluster analysis was performed. Results The countries showed inter-organisation variability in implementation and performance of the haemovigilance function. The overall median score (all sub-indicators) was 44 % (range: 7.5 % - 70 %). The lowest average performance scores were for the arrangement for effective organisation and coordination (35 %) and human resources (35 %) indicators. The highest average scores were observed for the mechanism to promote transparency and mechanism to monitor regulatory performance indicators (50 % and 60 %, respectively). We identified clusters of best-implemented sub-indicators from the procedures for haemovigilance and poorly implemented sub-indicators from the legal provisions, regulations and guidelines for haemovigilance and human resources. Conclusions Implementation of sub-indicators and performance of haemovigilance systems varied greatly for all countries with a few countries performing reasonably well in the implementation of some sub-indicators under procedures for haemovigilance. Most countries were poorly implementing sub-indicators in the legal provisions, arrangement for effective organisation and human resources indicators. The legislative provisions in most countries were at a nascent stage. There is a need to set up targeted and customised technical support coupled with prioritised interventions to strengthen the capacities of NRAs.